2003
DOI: 10.1152/ajpregu.00255.2003
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension alters GABA receptor-mediated inhibition of neurons in the nucleus of the solitary tract

Abstract: . Hypertension alters GABA receptor-mediated inhibition of neurons in the nucleus of the solitary tract. Am J Physiol Regul Integr Comp Physiol 285: R1276-R1286, 2003 10.1152/ajpregu. 00255.2003.-Previous studies have demonstrated that microinjection of baclofen, a GABA B receptor agonist, into the nucleus of the solitary tract (NTS) results in an enhanced pressor response in hypertensive (HT) rats compared with normotensive (NT) rats, suggesting a possible alteration in the responses of neurons in this area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 20 publications
(36 reference statements)
3
47
1
Order By: Relevance
“…Baclofen decreases the action potential discharge of NTS neurons receiving baroreceptor afferent inputs 6,8 and induces a pressor response. 3 Activation of GABA B receptors can presynaptically inhibit excitatory neurotransmitter release and decrease postsynaptic neuronal excitability via activation of a potassium conductance, 13 thus reducing the transmission of baroreceptor afferent inputs to other sites in baroreflex pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baclofen decreases the action potential discharge of NTS neurons receiving baroreceptor afferent inputs 6,8 and induces a pressor response. 3 Activation of GABA B receptors can presynaptically inhibit excitatory neurotransmitter release and decrease postsynaptic neuronal excitability via activation of a potassium conductance, 13 thus reducing the transmission of baroreceptor afferent inputs to other sites in baroreflex pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from this laboratory have demonstrated that renal-wrap hypertension is associated with increased GABA B receptor-mediated inhibition of baroreceptor-evoked discharge in NTS neurons 8 and increased expression of GABA B receptor mRNA in the NTS. 7 To clarify GABA B receptor-mediated cellular mechanisms in the neuronal adaptations to chronic hypertension, the present study investigated the postsynaptic effect of baclofen on NTS neurons receiving monosynaptic afferent inputs from baroreceptors and the influence of chronic hypertension on the postsynaptic response to baclofen.…”
mentioning
confidence: 87%
“…Disruptions in local NTS GABAergic transmission profoundly upsets homeostatic systems, including respiratory (Wasserman et al 2002), gastrointestinal (Travagli et al 2006), and cardiovascular systems (Mei et al 2003). In the case of anesthetics, targets within NTS include greatly enhanced GABAergic transmission at second-order NTS neurons (McDougall et al 2008a), as well as descending GABAergic inputs (Jia et al 1997;Jordan et al 1988).…”
Section: Homeostatic Reflex Integrationmentioning
confidence: 99%
“…Block of GABAergic signaling in the NTS broadly impacts cardiovascular, respiratory, and gastrointestinal regulation (Andresen and Mendelowitz 1996;Kubin et al 2006;Travagli et al 2006). GABA mechanisms may be altered during disease states such as hypertension (Mei et al 2003). Despite this rich physiological background, less is known about the precise patterns of organization of the relationship between ST afferents and the various potential pathways within NTS (i.e., intra-NTS) that control of GABAergic neurons, especially in the absence of anesthetics that broadly facilitate GABA transmission (McDougall et al 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…Arterial baroreceptors and respiratory afferents terminate within medial portions of the caudal NTS and are a source of excitatory glutamatergic input onto second-order NTS neurons (Mendelowitz et al, 1992;Doyle & Andresen, 2001; Kubin et al, 2006). GABAergic transmission in NTS is also critical to normal cardiorespiratory reflex performance Kubin et al, 2006) as well as pathophysiological conditions (Urbanski & Sapru, 1988;Callera et al, 2000;Mei et al, 2003;Tolstykh et al, 2004).…”
Section: Introductionmentioning
confidence: 99%